On the Impact of Predicate Complexity in Crowdsourced Classification Tasks; Web Search and Data Mining, WSDM 2021 - Ramirez J. Jorge; Baez M. Marcos; Casati F. Fabio; Cernuzzi L. Luca; Benatallah B. Boualem; Taran Е. А. Ekaterina Aleksandrovna; Malanina V. A. Veronika Anatolievna (2021, 2021)
Title screen